(3ZfjI GdeJedj aj TQM efjI GdeUdjs - (3GdMdHj, EHQGgje Hf eMeO EHQGgje, J (B956 (3g`s
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg LGYd GdUdGI YeGO GdOjf hYJGO GdeJbjf hdeG cGfJ GdUdGI PQhI SfGegG hYehO bjGegG hChd eG jSCd Yfg GdYHO aj GdYbHi hcGf GdcJGH GdeSei HefjI GdeUdj hZfjI GdeHJOj ef CMSf eG Ufa aj HjGfgG CMHHJ Cf CUfY dg TQMG hSejJg ZfjI GdeJedj aj TQM efjI GdeUdjs
(3BNQgG (B:s
(3ceG Cfg jUQ HgG Ydi JQc GdRjfI EPG CQGOgG hGdELGHI Edi aQGTg EPG OYGgG hGdNQhL HZjQ EPfg hEf de JfJg Yf JQcgG HGdVQH jWdbgG hdh de jcf bGOQG Ydi fgQgG s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B1 / 66s
(3eYLe GdeDdajf (B1 / 55s
(3cTa GdXfhf (B2 / 1886s
(3TPQGJ GdPgH (B8 / 308s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdMfHdjs